Accelerated 3-Year MD Pathway Programs: Graduates' Perspectives on Education Quality, the Learning Environment, Residency Readiness, Debt, Burnout, and Career Plans. (26th January 2022) - Leong, Shou Ling; Gillespie, Colleen; Jones, Betsy; Fancher, Tonya; Coe, Catherine L.; Dodson, Lisa; Hunsaker, Matthew; Thompson, Britta M.; Dempsey, Angela; Pallay, Robert; Crump, William; Cangiarella, Joan
Abstract : Purpose: To compare perception of accelerated and traditional medical students, with respect to satisfaction with education quality, and the learning environment, residency readiness, burnout, debt, and career plans. Method: Customized 2017 and 2018 Medical School Graduation Questionnaires (GQs) were analyzed using independent samples t tests for means and chi-square tests for percentages, comparing responses of accelerated MD program graduates (accelerated pathway [AP] students) from 9 schools with those of non-AP graduates from the same 9 schools and non-AP graduates from all surveyed schools. Results: GQ completion rates for the 90 AP students, 2, 573 non-AP students from AP schools, and 38, 116 non-AP students from all schools in 2017 and 2018 were 74.4%, 82.3%, and 83.3%, respectively. AP students were as satisfied with the quality of their education and felt as prepared for residency as non-AP students. AP students reported a more positive learning climate than non-AP students from AP schools and from all schools as measured by the student–faculty interaction (15.9 vs 14.4 and 14.3, respectively; P < .001 for both pairwise comparisons) and emotional climate (10.7 vs 9.6 and 9.6, respectively; P = .004 and .003, respectively) scales. AP students had less debt than non-AP students ( P < .001), and more planned to care for underserved populations and practice family medicine than non-AP students from AP schools (55.7% vs 33.9% and 37.7% vs 9.4%; P = .002 and < .001, respectively). Family expectations were a more common influence on career plans for AP students than for non-AP students from AP schools and from all schools (26.2% vs 11.3% and 11.7%, respectively; P < .001 for both pairwise comparisons). Conclusions: These findings support accelerated programs as a potentially important intervention to address workforce shortages and rising student debt without negative impacts on student perception of burnout, education quality, or residency preparedness.